PELAKSANAAN KEBIJAKAN TENTANG PROGRAM PERLINDUNGAN ANAK DI KABUPATEN MALANG - Leony Eterna; Dody Setyawan; Emei Dwinanarhati Setiamandani (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2022)
The existence of acts of violence against children both physically and psychologically in Malang Regency requires the attention of many people. Protection of children is the responsibility of the local government in this case is the Department of Women's Empowerment and Child Protection Malang Regency. The purpose of this study was to determine the implementation of policies regarding child protection programs in Malang Regency. This study uses the perspective of Charles O. Jones and uses descriptive qualitative research methods. Collecting data in this study using interviews, observation, and documentation. The determination of informants was carried out purposively with the key informant being the head of the Division of Women's Empowerment and Special Protection for Children. Meanwhile, other informants are Women and Children Empowerment Analysts, and victims' companions. Data analysis was carried out with data reduction techniques, data presentation, and drawing conclusions with the validity of the data using triangulation. The results of this study indicate that the implementation of the child protection program carried out by the Department of Women's Empowerment and Child Protection in Malang Regency consists of three activities, namely organizing, namely teamwork and the interpretation is the preparation and implementation of the program, and application, namely services and providers of goods and services according to the purpose. The supporting factors in the implementation of this program are the cooperation and accountability of the implementers of the child protection program and public awareness to make complaints directly or through the Wadool DP3A application. While the inhibiting factors are the problem of limited funds and the facilities for providing safe houses or shelters that are still not maximized.Adanya tindak kekerasan terhadap anak baik dalam bentuk fisik maupun psikis di Kabupaten Malang memerlukan perhatian banyak kalangan. Perlindungan terhadap anak merupakan tanggung jawab Pemerintah Daerah dalam hal ini adalah Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Malang. Tujuan penelitian ini adalah untuk mengetahui pelaksanaan kebijakan tentang program perlindungan anak di Kabupaten Malang. Penelitian ini menggunakan perspektif Charles O. Jones dan menggunakan metode penelitian deskriptif kualitatif. Pengumpulan data dalam penelitian ini menggunakan wawancara, observasi, dan dokumentasi. Penentuan informan dilakukan secara purposive dengan key informan adalah kepala Bidang Pemberdayaan Perempuan dan Perlindungan Khusus Anak. Sedangkan informan lainnya adalah Analis Pemberdayaan Perempuan dan Anak, dan pendamping korban. Analisa data dilakukan dengan teknik yaitu reduksi data, penyajian data, dan penarikan kesimpulan dengan keabsahan data menggunakan triangulasi. Hasil penelitian ini menunjukkan bahwa pelaksanaan program perlindungan anak yang dilakukan oleh Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Malang terdiri dari tiga aktivitas yaitu pengorganisasian ialah kerja sama tim dan sumberdaya, interpretasi ialah penyusunan dan pelaksanaan program, dan aplikasi ialah pelayanan dan penyedia barang dan jasa sesuai tujuan. Adapun faktor pendukung dalam pelaksanaan program ini adalah adanya kerjasama dan pertanggungjawaban para pelaksana program perlindungan anak dan kesadaran masyarakat melakukan pengaduan langsung maupun melalui aplikasi Wadool DP3A. Sedangkan faktor penghambat adalah masalah pendanaan yang terbatas dan fasilitas penyedian rumah aman atau shelter yang masih belum maksimal.